Supplementation of infant formulas with recombinant human lactoferrin and/or galactooligosaccharides increases iron bioaccessibility as measured by ferritin formed in Caco-2 cell model. (November 2016) - Aly, Esmat; López-Nicolás, Rubén; Darwish, Aliaa Ali; Frontela-Saseta, Carmen; Ros-Berruezo, Gaspar
Abstract: Recently, lactoferrin (Lf), a glycoprotein belonging to transferrin family, has received more attention for the discovery of its wide spectrum of functionalities. Among its important functionalities is its ability to bind Fe and its high stability against in vitro digestion. Galactooligosaccharides (GOS) also has functionality related to Fe bioaccessibility and it also positively affect Lf stability. This study aimed to evaluate the functionality of recombinant human Lf (rhLf) and GOS as factors that improve iron bioaccessibility in human milk. In this study, rhLf and GOS were added to First Infant Formula (FIF) in three concentrations (0.10, 0.15 and 0.20 and 3.3, 5 and 10 g 100 mL − 1 of the reconstituted formula, respectively), whether alone or in combination. In vitro digestion model was applied to different infant formulas to evaluate Fe solubility and the obtained digests were added to Caco-2 cell line to determine Fe bioaccessibility through the measurement of synthesized ferritin. The obtained results revealed that supplementation of formulas with rhLf and GOS enhanced Fe solubility to 66–97% which turns in an improvement of Fe bioaccessibility. Caco-2 cell ferritin content ranged from 6 to 46 ng per mg cell protein with 5–7.5 fold increases in cells incubated with digested samples containing both rhLF and GOS. Although mineral solubility is the most important factor, which affects on Fe bioaccessibility, other factors may also interfere with it, such as the expression of divalent metal transporter 1 (DMT1). The findings also revealed that rhLf is a highly stable protein, especially in the presence of GOS and more researches are needed to clarify this hidden effect of GOS. Thus, rhLf and GOS together are prominent components of human milk could improve Fe bioaccessibility and it is noteworthy that these finding must be taken into account during infant formula evolution to prevent some disease related to Fe deficiency. Graphical abstract: Highlights: This is a novel study of nutritional functionality of human lactoferrin and galactooligosaccharides in infant formula. Recombinant human lactoferrin (hLf) determines iron solubility as well as bioaccessibility in infant formula High percentage of hLf remains stable after in vitro digestion (IVD) and modulates iron bioaccessibility Released peptides after IVD of hLf increase Fe solubility and intestinal cell uptake